Evaluasi Tipe Dan Biaya Transportasi Dalam Rantai Pasok Sayuran Oyong: Studi Kasus Disektor Agribisnis - Angelica Salsabila; Mutiara Alya Ramadhina; Nadia Rosa; Haura Izdihar Ardhilya; Sabilinnisa Azahra (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
This research aims to Evaluate various types of transportation used in the supply chain of angled luffa (sponge ground) ,compare the costs of each transportation type and deciding the most efficient transportation option to enchance the supply chain efficiency of luffa vegetables. The method that we used in this research is a quantitative approach to calculate and compare transportation costs based on vehicle types and a qualitative approach to comprehend the factors that influencing transportation type selection. The result of this research are expected to assist agribusiness actors and luffa vegetable distributors in selecting the optimal transportation type and reducing logistics costs, thereby increasing the profit margins.